Problems in the Training of Japanese Language Teachers in Malaysia and their Countermeasures - Yoko Kami (Journal of Modern Languages)
This study outlines the problems of the Japanese language teachers encountered during training as the Japanese language teachers in Malaysia. It also considers the background of Japanese language teaching in Malaysia in the years between 1956 -1983.